IMPLEMENTATION OF DISTANCE LEARNING TECHNOLOGIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Distance education is becoming popular in a modern society. People of all ages and of different professions have an opportunity to learn from a distance. The emergence of distance learning entailed the need for the development and implementation of distance learning technologies. Like all new technologies, distance learning has certain advantages and disadvantages.